Real silver and its investment and business options - Novotný, Josef; Polách, Jiří (My University, 2016)
The article deals with investment and business opportunities offered by silver. Silver is the metal used in industry and for investing at financial markets. The main problem related to this real commodity is the issue of “the undervaluation” of its investment options, if compared to gold. If considering silver as the investment option, its investment potential is significantly enhanced by its industrial usage. The aim of this paper is to highlight business and investment opportunities for both professionals and non professional investors at the commodity markets. The price growth of this investment and industrial metal can generate profits for the investors. And on the other hand, industries which cannot do without silver in their production may efficiently utilize the knowledge of setting up its price at the markets.
Investiční a podnikatelské možnosti reálného stříbra
Keywords: investment; silver; business; commodity; industrial metal; investice; stříbro; podnikání; komodity; drahý kov